The Effect of Profitability on Firm Value With Leverage as The Intervening Variable and Company Size as The Control Variable - Nabila Alya Alexandra; Akhmadi Akhmadi; Helmi Yazid (Institute of Advanced Knowledge and Science, 2025)
This research was conducted to determine the influence of profitability to firm value. Specifically, to test whether leverage is able to mediate profitability on firm value and test whether firm size contributes to strengthen firm value. The writer conducted research on stock index of LQ45 company listed on the IDX which are listed on the Indonesia Stock Exchange (IDX) in 2018 – 2022. Secondary data was obtained from www.idx.co.id. The results of the study show that profitability has a significant effect on firm value, leverage is able to mediate the relationship between profitability and firm value. In addition, the firm value becomes strong with firm size as control variable. The implications of this research are that the enhancement of profitability give trust to the investor so firm value will increase and leverage can strengthen the influence of profitability on firm value positively.